Changing Finger Movement Perception: Influence of Active Haptics on Visual Dominance - Boban, Loën; Pittet, David; Herbelin, Bruno; Boulic, Ronan (Frontiers in Virtual Reality, 2022)
The perception of one’s own body is a complex mechanism that can be disturbed by conflicting sensory information and lead to illusory (mis-)perceptions. Prominent models of multisensory integration propose that sensory streams are integrated according to their reliability by approximating Bayesian inference. As such, when considering self-attribution of seen motor actions, previous works argue in favor of visual dominance over other sensations and internal cues. In the present work, we use virtual reality and a haptic glove to investigate the influence of an active haptic feedback on one’s visual and agency judgments over a performed finger action under experimentally manipulated visual and haptic feedbacks. Data overall confirm that vision dominates for agency judgment in conditions of multisensory conflict. Interestingly, we also show that participants’ visual judgment over their finger action is sensitive to multisensory conflicts (vision, proprioception, motor afferent signals and haptic perception), thus bringing an important nuance to the widely accepted view on a general visual dominance.